Isolation, characterization and phylogenetic analysis of dye decolorizing bacteria from textile sludge - Sultana, Sumaiya (Brac University, 2021)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Microbiology, 2020.